How predictive is the fasting blood glucose in diagnosing gestational diabetes mellitus ? - Arasalingam, A.; Wijeratne, A.S.D.S.; Warnakulasooriya, A.M.; Wijeyaratne, C.N. (My University, 2004)
OBJECTIVE: To determine the sensitivity, specificity and predictive value of fasting plasma glucose as a basic screening test for gestational diabetes mellitus. METHOD: Cross sectional retrospective analysis 999 consecutive 75g oral glucose tolerance tests (OGTT) were carried out on pregnant women between 20-24 weeks of gestation with risk factors for gestational diabetes at the department of Obstetrics and Gynaecology, Faculty of Medicine, Colombo between April 2003 to November 2003 and were analyzed. RESULTS: (PLEASE AQUIRE THE FULL PAPERS FOR THE DATA TABLE) Receiver operating characteristic curve (ROC curve) showed that the accuracy of FBS as satisfactory (Area under the curve = 0.84) The cut off value that yielded a satisfactory sensitivity and specificity was 86 mg/dl. CONCLUSIONS: The value of fasting plasma glucose in the 75g oral glucose tolerance test used in the screening for gestational diabetes mellitus is improved by lowering the cut off value to 86 mg/dl.